A descriptive study on sociodemographic features and process of dependence in alcohol dependent patients within remission period - İlhan, İnci; Demirbaş, Hatice; Doğan, Yıldırım B. (Journal of Dependence, 2002)
Objective: It has been aimed to obtain definitive data about biopsychosocial features and alhohol use histories of alcohol dependent patients.Method: Questions regarding alcohol use histories, biopsychosocial features and treatment methods received have been asked to 53 patients diagnosed with alcohol dependence who had been remaining in remission for at least 12 weeks.Results: Mean age of beginning of alcohol use was 15.2. It was determined that effects of alcohol use at the beginning consisted mainly of negative ones, once dependence had developed the most complained negative effects were black-out and harming oneself/others, and insomnia, anxiety/depression and lethargy were the most frequent withdrawal symptoms. Family history of problematic drinking was determined in 45.3% of alcoholic patients, and familial problems that they related with alcohol (73.6%) was found to be the foremost reason for their decision for treatment.Conclusion: It has been tried to determine the progress of dependence for hospitalized patients who were in remission period. However a comparative investigation of similar features in alcohol dependent outpatients who come with relapse would provide further information on determinants of relapse and remission in alcohol dependence.
Keywords: Alcohol dependence; remission; sociodemographic variables